Geological Investigations in Ellesmere Island, 1952 - Troelsen, J.C. (ARCTIC, 1952)
Contains an account of the author's studies of the Canyon Fjord region (ca. 80 N, 82 W), especially of Caledonian Bay, east of Eureka in summer of 1952. Studies of the Ellesmere Island mountains; and previous expeditions to Canyon Fjord are noted; the author's itinerary and his geological investigations are reported, proving the essential correctness of Lauge Koch's early contention that the mountains of North Greenland and Ellesmere Island are of the Caledonian age; author's collecting of plants and microfauna, observations on animals (muskox, hare, fox wolf, seals, birds) are mentioned. Bibliography (4 items).